2015
DOI: 10.14503/thij-14-4971
|View full text |Cite
|
Sign up to set email alerts
|

Present-Day Hospital Readmissions after Left Ventricular Assist Device Implantation: A Large Single-Center Study

Abstract: A Large Single-Center StudyLeft ventricular assist device (LVAD) C irculatory support with left ventricular assist devices (LVADs) has emerged as a powerful therapy that can improve outcomes in patients who have advanced heart failure (HF) refractory to medical therapy.1-3 The scarcity of donor organs severely limits transplantation as an option for patients with advanced HF; moreover, transplant patients need lifelong immunosuppression, the medications for which can have their own serious side effects. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…Our findings highlight the challenge of repeated read-missions after LVAD implantation. The readmission rate in our cohort was 1.81 events/y, similar to the rates of other reports (≈2.0 events/y) [12][13][14] and serves as a reminder that adverse events remain a significant barrier to expanded use of LVADs. Baras Shreibati et al 2 have demonstrated that the costeffectiveness of LVAD therapy continues to be adversely affected by frequent readmissions.…”
Section: Survival and Readmission During Lvad Supportsupporting
confidence: 89%
“…Our findings highlight the challenge of repeated read-missions after LVAD implantation. The readmission rate in our cohort was 1.81 events/y, similar to the rates of other reports (≈2.0 events/y) [12][13][14] and serves as a reminder that adverse events remain a significant barrier to expanded use of LVADs. Baras Shreibati et al 2 have demonstrated that the costeffectiveness of LVAD therapy continues to be adversely affected by frequent readmissions.…”
Section: Survival and Readmission During Lvad Supportsupporting
confidence: 89%
“…Existing data report remarkably high hospital readmission rates after LVAD [ 33 , 34 ]. The leading causes for hospital readmission in this population range from non-cardiac comorbidities [ 35 ], gastrointestinal bleeding [ 36 ], and device component infection [ 37 ] to recurrent heart failure [ 38 ] and progression of cardiac pathology [ 37 ]. The current study represents the challenges inherent in attempting to predict a very common outcome, and the need for further study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, patients in the TI cohort reported a mean INR of 2.4 6 0.4 and spent 72.2% of the TTR, possibly contributing to the reduced readmission rates based on major bleeding of 20.8% (TI) versus 36.4% in the UC group. This interpretation is supported by previous reports (16,21) that bleeding is the most common postoperative event in these patients. As VAD patients with elevated MAP are at an increased risk for pump thrombus or stroke (3,4,22), another positive effect of the telephone intervention algorithm is the enhanced blood pressure management seen in the TI versus UC group, resulting in a significantly lower MAP during follow up.…”
Section: Discussionmentioning
confidence: 99%
“…Preventing these adverse events or at least detecting them at an earlier, less urgent, stage must be the focus in VAD patient management to improve outcomes. While some centers report routine phone calls or at least phone contact to the patient or caregiver in addition to consensus‐based VAD outpatient practices, this is the first study reporting the implementation of a standardized telephone intervention algorithm. By means of a graphical user interface all problems detected on call were categorized fully, automatically based on an algorithm in five levels of severity and triaged in a standardized manner by the VAD Coordinator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation